Polimorfismo do gene SPi2 na obstrução recorrente das vias aéreas e na doença inflamatória das vias aéreas em cavalos puro sangue de corrida - Silva, Aline Correa da (2008)
Recurrent airway obstruction (RAO) and inflammatory airway disease (IAD) show high prevalence and are economically important in equine athletes. RAO is considered a multifactorial disease due to genetic and environmental components in their patophysiology. The aim of this study was to determine the presence of polymorphism at exons 2, 3, 4 and 5 of the SPi2 gene and a possible association between them and ORA or IAD on 51 thoroughbred horses through single-strand conformational polymorphism (SSCP). Exons 2, 3 and 4 of the Spi2 gene showed no polymorphism. On exon 5, 3 alleles and 6 genotypes were identified. Frequency of allele A (0.6388) and genotype AA (0.3888) were higher in horses affected by RAO but no association was found between any polymorphism and horses with RAO or IAD.